PENGARUH GAYA KEPEMIMPINAN MICROMANAGE DIMEDIASI EFIKASI DIRI TERHADAP KREATIVITAS KERJA KARYAWAN GENERASI Z - Boy Andika Sinaga (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2025)
. This study was conducted to prove that self-efficacy plays an important role in mediating the influence of micro leadership style on the work creativity of generation Z employees. The sampling technique used non-probability sampling with a sample size of 203 respondents from 6 employment sectors in Riau Province. The sample in this study came from the generation Z population born between 1997 and 2012. The variables used in this study were micromanagement leadership style as an independent variable, self-efficacy as a mediating variable and work creativity as a dependent variable. The data collection technique used a questionnaire distributed via google form and then analyzed using Smart-PLS 3. Analysis of the results of the outer model of the study obtained that all indicators and variables used were valid and reliable. In addition, an inner model analysis was carried out, the model used was fit and all hypotheses in the study were accepted. Micromanagement leadership style and self-efficacy have a significant positive effect on work creativity, micromanagement leadership style has a significant positive effect on work creativity and micromanagement leadership style through self-efficacy has a significant positive effect on work creativity. Managerial implications show that generation Z needs leaders who provide clear instructions and feedback in supporting work.